Association between maternal age and outcomes in Kawasaki disease patients - Wei-Dong Huang; Yu-Ting Lin; Zi-Yu Tsai; Ling-Sai Chang; Shih-Feng Liu; Yi-Ju Lin; Ho-Chang Kuo (BMC, 2019)
Abstract Background The etiology of Kawasaki disease (KD) is still unknown; perinatal factors may have role with few studies. This study was aim to survey the perinatal factors and clinical outcome of KD, including coronary artery lesion (CAL) formation and intravenous immunoglobulin (IVIG) treatment response. Methods We enrolled a total of 185 KD patient-caregiver dyads in this study using questionnaires. The questionnaire included two categories: children's characteristics, which consisted of age at disease onset, gender, gestational age at delivery, birth body weight, delivery methods, and breastfeeding status, and caregivers' characteristics, which consisted of parents or not, education levels, maternal age at giving birth, total number of offspring, and family income. We analyzed the association of these factors with CAL formation and IVIG treatment response of KD. Results KD patients with CAL formation had a higher maternal age than non-CAL patients (32.49 ± 3.42 vs. 31.01 ± 3.92 years, p = 0.016). We also found that maternal age ≥ 32 years group had a higher rate of having KD patients with CAL (39/81 vs. 24/74, odds ratio 1.935, 95% confidence interval [1.007, 3.718], p = 0.047). The maternal age ≥ 35 years group had a higher rate of having KD patients with IVIG resistance (6/31 vs. 6/116, odds ratio 4.400, 95% confidence interval [1.309, 14.786], p = 0.01). There was no significant difference in either CAL formation or IVIG resistance in KD with regard to patient's age at disease onset, gestational age, birth body weight, delivery methods, breastfeeding, caregiver type, caregivers' education level, total number of offspring, or family income (p > 0.05). Conclusions This study is the first to report that maternal age is significantly associated with CAL formation and IVIG resistance in KD. We hypothesize that a maternal age less than 32 years would benefit KD offspring.